1992
DOI: 10.1017/s0022029900027163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of methionyl bovine somatotropin in a prolonged-release vehicle on milk production, hormone profiles and health in dairy cows

Abstract: Milk production of dairy cows in 14 herds was increased by 3 -8-32'l % by the administration of recombinant methionyl bovine somatotropin (bST) in a sustained-release vehicle at 14 d intervals at 40-94 d post partum. A greater response in multiparous than in primiparous cows was found in cows turned out to graze spring pasture. Administration of recombinant bST resulted in elevated plasma bST during the first 9 d after injection. Clinical characteristics such as respiration, heart rate and body temperature wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…Plasma glucose level (mg/dl) in buffaloes during different fortnights suggested that there was no significant effect of treatment and period on glucose concentration due to rbST injection. The present finding is similar to earlier reports of Skarda et al (1992) and Abas and Ozpiner (2001). No change in the blood glucose level observed in this study may be suggestive of the fact that the injected dose of rbST does not have any influence on gluconeogenesis as have been observed by Fullerton (1989).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Plasma glucose level (mg/dl) in buffaloes during different fortnights suggested that there was no significant effect of treatment and period on glucose concentration due to rbST injection. The present finding is similar to earlier reports of Skarda et al (1992) and Abas and Ozpiner (2001). No change in the blood glucose level observed in this study may be suggestive of the fact that the injected dose of rbST does not have any influence on gluconeogenesis as have been observed by Fullerton (1989).…”
Section: Discussionsupporting
confidence: 94%
“…Concomitant to the findings of the present study, Bauman et al (1985), Burton et al (1991), Lean et al (1992) and Skarda et al (1992) reported higher milk production due to rbST injection. Bauman et al (1985) recorded 23-41% higher milk yield in the rbST injected dairy cows as compared to that of non injected group.…”
Section: Discussionsupporting
confidence: 87%
“…A number of studies have noted the effect of bST on bovine health in terms of risk of clinical mastitis, reduction in fertility and risk of developing clinical signs of lameness (Dohoo et al, 2003). The adverse effects of exogenous bST have also been reported in other animal species (Skarda et al, 1992). The changes in relative mass of many organs and tissue growth following bST administration have also been reported (Moallem et al, 2004), which may reflect changes in bodily functions.…”
Section: Introductionmentioning
confidence: 86%